SINTESIS SOLUSI ISLAM TERHADAP POLA KOMUNIKASI DESTRUKTIF ‘THE FOUR HORSEMEN’ DALAM PERNIKAHAN: KAJIAN TEORETIS DAN PRAKTIS - Muhammad Fariq Firdaus; Akhmad Husaini (LPPM STAI Muhammadiyah Probolinggo, 2025)
Destructive communication in marriage is one of the main causes of damaged relationships between spouses. John Gottman identified four negative communication patterns known as The Four Horsemen: criticism, contempt, defensiveness, and stonewalling, which have been proven to predict divorce. This study aims to analyze and synthesize the solutions offered by Gottman through The Antidotes with the principles of communication in Islam. Using a qualitative descriptive approach and a library research method, this study analyzes primary sources from Gottman's theory and widely recognized Islamic references. The findings show that Islamic solutions not only align with Gottman's psychological approach but also reinforce it with spiritual values such as self-reflection (muhasabah), emotional regulation, and mutual consultation (shura). This synthesis offers a more holistic approach to building healthy marital communication that is also spiritually meaningful. The study is expected to enrich the literature on marital communication by integrating modern psychology with Islamic values.